Perancangan Aplikasi Enkripsi Menggunakan Algoritma Vigenere Cipher Berbasis Web - Rohani, Rohani (Journal of Computer Science and Information System(JCoInS), 2021)
Security and privacy is needed when exchanging important information in the era of information and communication technology today. One way that can be used to make an important information can not be understood by unauthorized people is encrypt information so that the information is difficult and can not even be understood by others. Encryption cryptography is used to convert key information into ciphers to encrypt the required sentence want encrypted and memelurkan key. One way to encrypt important information by using the method vigenere cipher algorithm, encryption is a way to produce by processing the original text letters into numbers using mathematical operations. The key used vigenere cipher algorithm that is shaped, in the form of a row of letter keys that will allow each original text to be encrypted. Results of encryption using methods vigenere cipher that can encrypt important information by means of encrypting the data into a code that can not be read by unauthorized people and this application can also restore data that has been encrypted into data that can be read by means of decrypting data has been encrypted.